Women writers and interdisciplinary and territorial experiences in literary education: the case of Maria Ibars in Denia (Ogigia. Revista Electrónica de Estudios Hispánicos, 2023)
This research analyzes the contribution of a writer in the configuration of a territorial brand, based on literature, from the link between the work of the writer Maria Ibars and the city of Denia (Marina Alta). Maria Ibars was a teacher and writer (1892-1965) born in Valencia but rooted in Dénia. Her works, narrative and poetic, have a strong link with the territory, specifically with the seaside town of Dénia and the towns that live in the shadow of Montgó, the mythical mountain, the center of the author's literary work. The town council of Dénia has been weaving a cultural project around the figure of the writer from two literary routes, prepared in collaboration with the Institut d'Estudis Comarcals, which are the basis of various educational, social, cultural and tourist proposals. The aim of this study is the analysis of the social impact of this writer in the dynamization of the environment. We will take as a basis the IX Jornades Literatura Territori Educació held between April 29 and May 1 in Denia, which paid tribute to the writer and were an impetus for research and educational, creative and multidisciplinary experiences.
Keywords: women writers; literary education; literary routes; interdisciplinarity; territory